Online Media Literacy among Gen Z in Kendari City in the Post Truth Era - Sri Hadijah Arnus; Wahyuni Husain; Dini Asriani (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2023)
Information and communication technology development allows every individual to obtain and produce information quickly. This development brings us to the post-truth era, where truth is relative. Generation Z is among the most intense social media user groups. Based on this, this research wants to look at online media literacy among Gen Z in Baruga District, Kendari City, in the post-truth era. This research method is descriptive qualitative by analyzing the individual competence framework, namely data analysis through data analysis techniques, to determine online media literacy skills from three levels: basic, medium, and advanced. The study results show that the online media literacy level of gen z Kendari City in responding to hoax news on social media is still at a basic level. The technical skill ability of Gen Z based on indicators of the individual competence framework is at a medium level. Critical understanding ability is still at the basic stage. Meanwhile, social competence, which consists of Communicative abilities, is still at a basic level. Gen z media literacy skills in Kendari City still need to be improved. Efforts that can be made to increase gen z online media literacy are conducting training related to online media literacy for gen z, both carried out by the local government and support from religious leaders.